THE ROLE OF THE POLICE AS MEDIATORS IN RESOLVING CRIMINAL CASES OF DOMESTIC PHYSICAL VIOLENCE THROUGH RESTORATIVE JUSTICE IN THE JURISDICTION OF THE BENGKULU CITY RESORT POLICE - Huda, Nur; Hatrik, Hamzah; Royan, Antory (Universitas Bengkulu, 2024)
Based on the data obtained in the resolution of criminal cases involving domestic physical violence through the restorative justice approach in the jurisdiction of the Bengkulu City Resort Police from 2019 to 2021, it has not been able to function optimally. This condition is because the police, particularly the investigators, await a settlement agreement between the parties involved and the withdrawal of complaints by the complainants. This condition raises the question of how the resolution through a restorative justice-based approach, carried out by the police as mediators, can be the best solution for resolving cases involving the parties through a restorative justice approach. This reason is what motivated the author to conduct this research. The methodology employed is empirical legal research, utilizing primary and secondary data. The data was analyzed qualitatively through a juridical lens, leading to inductive conclusions. Based on the results of this research, the following findings emerge: (1). The concept of restorative justice is employed in handling criminal cases with an emphasis on the integration of perpetrators, victims, and the community as a whole, seeking to find solutions and restore a positive relationship between the perpetrator of the criminal act. (2). The role of the police as mediators has yet to be optimally executed, primarily due to concerns and suspicions from the involved parties regarding potential bias by the police towards one party. Internally, the police have established regulations, such as the Telegram Letter from the Head of the Criminal Investigation Division Number S.T./583/VIII/2012 dated August 8, 2012. (3). Investigator's considerations as mediators in using the restorative justice-based approach to resolvedomestic physical violence within the jurisdiction of the Bengkulu Resort Police include the submission of peace agreements by both the victim and the perpetrator. This consideration is especially relevant in cases of minor physical violence, where the victim does not wish to prolong the case, and the interests of the victim in domestic violence are accommodated Keywords : Police Role, Mediator, Restorative Justice, Domestic Violence